Research on adaptive grasping with object pose uncertainty by multi-fingered robot hand. (6th April 2018) - Fan, Shaowei; Gu, Haiwei; Zhang, Yuanfei; Jin, Minghe; Liu, Hong
In the process of grasping objects by robot, the uncertainty of the object pose has greater impact on the stability of grasping. In this article, an adaptive grasping strategy is proposed to solve the problem of pose uncertainty in the grasping process. The strategy is based on the finger state function to switch control method, so as to realize the contact with the object by the fingers, and the application of grasp force to ensure the pre-grasp stability of the object; then, the object pose error is estimated through the contact between finger and object, and the pose error of the object is compensated according to the different error ranges to reduce the influence of the pose error on the grasp stability. Finally, the grasping experiments by humanoid robot are carried out to verify the performance of the adaptive grasping method proposed in this article.